Tandem Upgrading of Bio-Furans to Benzene, Toluene, and p-xylene by Pt1Sn1 Intermetallic Coupling Ordered Mesoporous SnO2 Catalyst - Xiao, Shoukang (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2024 Wiley‐VCH GmbH.